FAKTOR YANG MEMPENGARUHI PERMUKIMAN KUMUH DI KECAMATAN PADANG SELATAN - ramadhan, muhammad noval; Ramadhan, Risky (JURNAL BUANA, 2024)
Research objectives: 1) To find out the distribution pattern of slums in South Padang District. 2) To find out the factors that influence slum settlements in South Padang District seen from the characteristics of facilities and infrastructure. This research is a type of quantitative research using percentage descriptive methods and percentage descriptive analysis techniques. The results of this study: 1) The distribution pattern of slums in South Padang District was analyzed using the Average Nearest Neighbor in the ArcGIS Application. Then the pattern of slum settlements is Clustered or grouped with a Z-Score -8.343167 and a p-value of 0.000000. 2) Factors affecting slum settlements in South Padang District in terms of the characteristics of slum settlement facilities and infrastructure, namely, road conditions have experienced an increase in quality, initially the dominant road surface is dirt and paving, now paving is in fairly good condition, the condition of clean water infrastructure has been fulfilled and able to serve the needs of the community for their daily needs, the condition of the MCK on average has private MCK, the condition of garbage collection is still not able to serve the community, it is necessary to add 1 TPS in every RW and RT located in Seberang seberang Pagargam Village and Batang Arau Sub-District and improve the system waste transportation, and the effect that the existing drainage is not managed by the relevant agency, based on the results of interviews with residents, the drainage is every few months.